Characterization Ni Nanocatalyst on Si (100) Substrate By Sputtering Growth Methods - Patricia Lubis; Altje Latununuwe; Toto Winata (Jurnal Dosen Universitas PGRI Palembang)
AbstractCharacterization Ni metal nanocatalyst had been analyzed on Si (100) substrate with Sputtering Growth Methods. The sputtering conditions used were 4x10-1 torr in pressure; 1500C in temperature; 77.3 sccm in Ar gas flow; and 90,30,20 minutes in time depositions. After growth deposition, metal nanocatalysts were annealed in temperature 6000C for 30 minutes. Characterizations of Ni metal nanocatalysts were used Scanning Electron Microscopy (SEM) and Energy Dispersive Analysis X-Ray (EDAX) and we found the tendency of smallest structure with decrease of time deposition.Keywords: nanocatalyst, sputtering, anneal.